2241. Outcomes of Program Cell Death Protein 1 (PD-1) and Programmed Death-Ligand 1(PD-L1) Inhibitor Therapy in HIV Patients with Advanced Cancer. (26th November 2018) - Bari, Shahla; Chan, Austin; Jain, Sanjay; Hostler, Christopher
Abstract: Background: Due to HAART and consequent decline in mortality from infectious complications, HIV patients have an increasing burden of non-AIDS defining cancers. Immunotherapy, consisting of PD1/PDL1 inhibitors, has revolutionized the treatment of cancers but data on their safety and efficacy is unknown in HIV patients, as they were excluded from clinical trials due to concern for unforeseen side effects. Methods: This is the largest retrospective study, involving 17 patients with HIV, treated with one of the 4 PD-1/PD-L1 inhibitors (Nivolumab, Pembrolizumab, Atezolizumab, Durvalumab or Avelumab) for cancer.The objective of our study was to evaluate the efficacy and safety profile of PD-1 and PD-L1 inhibitors in Cancer patients with HIV and also to assess the impact of these drugs on HIV infection control, specifically CD4 count and HIV viral load. Results: Ten out of 17 patients responded to therapy. Of the 10 patients who responded to therapy, seven were alive and four were still on therapy. Ten patients including all seven non-responders died; nine died from cancer progression and one from sepsis after discontinuing HAART. The minimum duration of response was 15 weeks with one ongoing response at 34 weeks (similar to non HIV patients). Adverse events (Grade 1 or 2) were noted in seven patients while one stopped therapy due to pneumonitis. CD4 count was stable on treatment and HIV RNA was undetectable (became undetectable in one patient with initial low HIV viremia) (Table1). Conclusion: PD-1 and PD-L1 inhibitors have transformed cancer treatment. Our data shows that they have equal efficacy, tolerable side effects with no effect on HIV markers when used in HIV patients with cancer. We strongly advocate inclusion of HIV cancer patients in clinical trials and support the use of PD1/PDL1 inhibitors in them. Disclosures: All authors: No reported disclosures.